THE CONSTITUTIONAL FRAMEWORK OF FUNDAMENTAL RIGHTS IN PAKISTAN: ENFORCEMENT AND CHALLENGES AFTER THE 18TH AND 26TH AMENDMENTS - Taimur Abbas; Dr Naeem Ullah Khan (Policy Journal of Social Science Review, 2026)
The constitutional foundation of fundamental rights of the people in Pakistan is one of the key areas of democratic governance and constitutionalism in Pakistan. The Constitution of Pakistan 1973 provides for a wide-spectrum of civil, political, social and economic rights under Articles 8-28. The reality of the situation is that these rights are still not being effectively realised because of a variety of institutional shortcomings, political interference, judicial inadequacy and socio-economic disparities. The main objective of this research is to critically examine the constitutional form of the fundamental rights in Pakistan with particular focus on the effect of the 18th and 26th Constitutional Amendments. The method of this research is qualitative and doctrinal method that combines the provisions of the constitution, judicial decisions, constitutional literature, and comparative constitutional studies. The research shows that the 18th Amendment continued to advance democraticisation of parliament and provincial autonomy, while the 26th Amendment had many judicial and institutional changes with constitutional governance and accountability implications. However, theory and practice of the Constitution are not in harmony. The study finds that, in addition to constitutional protection, fundamental rights can only be effectively protected with the help of independent institutions, transparency of judiciary practices, accountability of administrations, and better access to justice. Keywords: Fundamental rights, constitution of Pakistan, 18th amendment, judicial independence, constitution law, rule of law https://doi.org/10.5281/zenodo.21714862